Marcin Kromer (1512–1589) w walce o reformę Kościoła w Polsce. „Sermo de tuenda dignitate sacerdotii” - Dziuba, Agnieszka (Symbolae Philologorum Posnaniensium Graecae et Latinae, 2022)
The author of this article discusses the circumstances of delivering a speech Sermo de tuenda dignitate sacerdotii by Martinus Cromerus, analyzes its content and style. Proves that iuvenilis sermo is worth attention because of the author’s great rhetorical workshop, excellent biblical and patrological preparation as well as general erudition. The speech was composed according to the priciples of classical rhetoric and it is inspired by the speeches of Cicero.